Gravitation and cosmology : principles and applications of the general theory of relativity - Weinberg, Steven; Weinberg, Steven (New Delhi, Wiley India, 1972)
Gravitation and Cosmology: Principles and Applications of the General Theory of Relativity.
Include bibliographical references ; Appendix 635-640p.; Index 641-657p.
Keywords: Astrophysics-relativity; Cosmology; General relativity; Gravitation; Physics